Uniqueness of weak solution for nonlinear elliptic equations in divergence form - Xu Zhang (International Journal of Mathematics and Mathematical Sciences)
We study the uniqueness of weak solutions for quasilinear elliptic equations in divergence form. Some counterexamples are given to show that our uniqueness result cannot be improved in the general case.